Human anatomy & physiology : - Martin, Terry R. (McGraw - Hill, 2004)
Thoroughly revised and designed to accompany Hole's Human Anatomy and Physiology, this laboratory manual provides increased emphasis on safety and includes several changes that make it more user-friendly.